Ginsenoside Rg1 Attenuates Cigarette Smoke-Induced Pulmonary Epithelial-Mesenchymal Transition via Inhibition of the TGF-β1/Smad Pathway. (13th August 2017) - Guan, Sibin; Xu, Weiguo; Han, Fengfeng; Gu, Wen; Song, Lin; Ye, Wenjing; Liu, Qian; Guo, Xuejun
Abstract : Epithelial-mesenchymal transition (EMT) is a process associated with airway remodeling in chronic obstructive pulmonary disease (COPD), which leads to progressive pulmonary destruction. Panax ginseng is a traditional herbal medicine that has been shown to improve pulmonary function and exercise capacity in patients with COPD. Ginsenoside Rg1 is one of the main active components and was shown to inhibit oxidative stress and inflammation. The present study investigated the hypothesis that ginsenoside Rg1 attenuates EMT in COPD rats induced by cigarette smoke (CS) and human bronchial epithelial (HBE) cells exposed to cigarette smoke extract (CSE). Our data showed that CS or CSE exposure increased expression of the mesenchymal marker α -smooth muscle actin ( α -SMA) and decreased expression of the epithelial marker epithelial cadherin (E-cad) in both lung tissues and HBE cells, which was markedly suppressed by ginsenoside Rg1. Importantly, CS-induced upregulation of TGF- β 1/Smad pathway components, including TGF- β 1, TGF- β R1, phospho-Smad2, and phospho-Smad3, was also inhibited by ginsenoside Rg1. Additionally, ginsenoside Rg1 mimicked the effect of SB525334, a TGF- β R1-Smad2/3 inhibitor, on suppression of EMT in CSE-induced HBE cells. Collectively, we concluded that ginsenoside Rg1 alleviates CS-induced pulmonary EMT, in both COPD rats and HBE cells, via inhibition of the TGF- β 1/Smad pathway.